2009
DOI: 10.1186/1476-0711-8-14
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of vacA, cagA and babA2 virulence markers in Helicobacter pylori strains isolated from Mexican patients with chronic gastritis

Abstract: Background: Helicobacter pylori has been strongly associated with chronic gastritis, peptic and duodenal ulcers, and it is a risk factor for gastric cancer. Three major virulence factors of H. pylori have been described: the vacuolating toxin (VacA), the cytotoxin-associated gene product (CagA) and the adhesion protein BabA2. Since considerable geographic diversity in the prevalence of H. pylori virulence factors has been reported, the aim of this work was to establish the H. pylori and vacA, cagA and babA2 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
29
6
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 44 publications
14
29
6
1
Order By: Relevance
“…A statistically significant association was observed between cagA, cagE, vacA genes and babA2 (p<0.05) ( Table 3), but other authors did not find any association between these pathogenicity genes in the samples they investigated 23,32,33 . Our data, however, supports the relationship between the genes cagA, cagE, vacA and babA2 that was described in previous reports [34][35][36][37] .…”
Section: Discussionmentioning
confidence: 84%
“…A statistically significant association was observed between cagA, cagE, vacA genes and babA2 (p<0.05) ( Table 3), but other authors did not find any association between these pathogenicity genes in the samples they investigated 23,32,33 . Our data, however, supports the relationship between the genes cagA, cagE, vacA and babA2 that was described in previous reports [34][35][36][37] .…”
Section: Discussionmentioning
confidence: 84%
“…On the contrary, Paniagua, et al 2009 [54] reported that no statistically significant association was observed between vacA s1, cagA and babA2 virulence markers and Abdullah, et al 2013[43] reported that babA2 positive strains were significantly more likely to be cagA positive and they did not find a significant association between cagA status and vacA s2, vacA m1, vacA m2 subtypes. As regards the relationship between H. pylori virulence factors and endoscopic findings, cagA positive isolates had the highest frequency, followed by vacA s1a and vacA m2 while babA2 positive isolates had the least frequency in most patients with PUD, NUD, gastritis and duodenitis.…”
Section: )[32]mentioning
confidence: 99%
“…2017; 10(12):e60947. (13,14). Numerous documents revealed that H. pylori expression babA are related to more severe mucosal cellular inflammation and increased risk of clinical outcome diseases like active gastritis, peptic ulcer, and gastric cancer (15).…”
Section: Discussionmentioning
confidence: 99%